High-Performance Tall Buildings: An Overview of Recent Developments - Kheir Al-Kodmany; Mir M. Ali (Encyclopedia, 2025)
The evolution of tall buildings has been shaped by distinct architectural styles, beginning around 1875 and progressing through various stylistic architectural movements. These changes were driven by advancements in structural engineering and digital design technologies, leading to greater experimentation with form and function. Energy and resource conservation of the late 20th century instigated a noteworthy focus on sustainability. Beyond that, the early 21st century saw a significant shift toward a new breed of tall buildings, a suitable architectural vocabulary for “high-performance” tall buildings, in which sustainability with a focus on energy efficiency is joined with the performance of other active and passive functional systems. This paper presents an overview of high-performance tall buildings by exploring key technologies, materials, innovations, safety, durability, and indoor environmental quality. Strategies that have emerged to address skyscrapers’ environmental and economic challenges are also crucial in such a building. It highlights the importance of optimizing and integrating building systems, improving energy efficiency, minimizing resource consumption, and ensuring long-term occupant health and productivity. Furthermore, this study identifies five key dimensions—structural materials and systems, energy-efficient design, high-performance façades, performance monitoring, and integrating building services systems—demonstrating how these factors contribute to environment-conscious urban development and resilient architectural and engineering design. It is concluded that these buildings are poised to redefine urban environments by leveraging advanced technologies, AI-driven management, IoT interconnectivity, health-focused elements, and climate resilience. Also, tall, high-performance buildings will be increasingly automated to an unknown limit, and AI will play a prominent role in the future.